Carbonic Anhydrase 4 Serves as A Novel Prognostic Biomarker and Therapeutic Target for Non-Small Cell Lung Cancer: A Study Based on TCGA Samples - Xu, Bo; Lou, Yang; Xu, Xiaoyi; Li, Xianshuai; Tian, Xin; Yu, Zhaonan; Chen, Xianguo (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Carbonic anhydrase 4 (CA4) is a member of a large family of zinc metalloenzymes that catalyze the reversible hydration of carbon dioxide and was found to have low expression in non-small cell lung cancer (NSCLC). However, the specific role of CA4 in NSCLC and the underlying mechanisms remain unknown. Methods: The bioinformatic analysis on lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) datasets downloaded from The Cancer Genome Atlas (TCGA) database was performed. We found that CA4 expression was lower in tumors than that in normal tissues, which were verified by Real-time PCR. Lower CA4 levels were significantly associated with higher T stages in LUAD and LUSC cohorts. Multivariate analysis showed that CA4 is an independent prognostic factor for NSCLC. Furthermore, the expression of CA4 also correlated with immune infiltration and drug sensitivity. Results: Ectopic expression of CA4 decreased NSCLC cell proliferation in vitro by CCK-8 assay. CA4 caused G0/G1 cell cycle arrest by cell experiments. Mechanistic studies found that CA affects the cell cycle and inhibits cell proliferation by downregulating the expression of CDK2. Conclusion: The present findings highlight the role of CA4 in NSCLC and identify CA4 as a potential novel diagnostic and prognostic biomarker for the treatment of NSCLC.
Keywords: diagnostic biomarker